Analisis Terhadap Alasan Memperingan dalam Putusan Mahkamah Agung Nomor 3287 K/PID.SUS/2019 - Tasya Renwarin, Chrisjane; Adhari, Ade (UNES Law Review, 2023)
Enforcement of criminal law at the examination stage in court hearings plays a crucial role in SPP. The court decision is the end of this stage. The heart of a court decision is the judge's legal considerations and ruling. The judge's legal considerations explain why his decision was such. One thing that is often included in the judge's legal considerations is the reason for mitigation which is the cause of the judge's decision regarding the sentence being reduced. In practice, the judge's legal considerations and rulings are not always in line with the Supreme Court's cassation decision Number 3287 K/Pid.Sus/2019. The type of research in this writing uses normative legal research, a type of secondary data with a library research method which is then analyzed using qualitative methods and drawing conclusions deductively. The reasons for mitigation in the court's decision are manifested in the judge's legal considerations. For reasons of mitigation, the judge handed down a lighter sentence to the defendant. The verdict, which carries a lighter sentence, is given by the panel of judges by including the reasons for mitigation in the legal considerations so that the Ratio Decidendi is created, and the decision can be justified. Article 95 of the Juvenile Criminal Justice System Law states that judges who make mistakes in deciding cases can receive punishment in the form of administrative sanctions in accordance with statutory provisions. In practice, in the Supreme Court's cassation decision Number 3287 K/Pid.Sus/2019, the panel of judges gave a lighter sentence decision than the public prosecutor demanded but did not explain the reasons for mitigation in their legal considerations, on the contrary what was explained was the reasons for aggravation, even though this is required in Law on Judicial Power to judges. Thus, the decision is contrary to the law, materially flawed and cannot be held accountable by the panel of judges because it does not present the Ratio Decidendi which is the mandate of Article 8 paragraph (2) of the Judicial Power Law that in considering the severity and severity of the crime, the judge must be obliged to clearly see the nature of the crime. good and bad of a defendant.